The Influence of Halal Labels on Cosmetic Products on Consumer Purchase Decisions in Indonesia - Suriati Suriati; Ichwan P. Syamsuddin; Dinah Husniah (JURNAL PENDIDIKAN IPS, 2025)
In recent years, the awareness of Muslim consumers in Indonesia towards halal products has increased significantly, not only in food and beverages, but also in cosmetic products. The halal label on cosmetics is one of the important factors in influencing purchasing decisions, especially in the midst of rampant imported products and global beauty trends. This study aims to determine the extent to which the halal label influences consumer purchasing decisions for cosmetic products in Indonesia. This study uses a quantitative approach with a survey method through distributing questionnaires to 200 Muslim respondents who actively use cosmetics. The data were analysed using simple linear regression to test the relationship between halal labels and purchasing decisions. The results showed that the halal label has a positive and significant influence on consumer purchasing decisions. Consumers feel more confident and safe in using halal-labelled cosmetic products because they are believed to be free from unclean and haram ingredients. In addition, the halal label also increases the perception of product quality and credibility in the eyes of consumers. These findings indicate that cosmetics manufacturers need to pay more attention to halal certification as an effective marketing strategy in the predominantly Muslim Indonesian market. The conclusion of this study confirms that the halal label is not just a religious symbol, but a strategic element in building consumer loyalty and confidence.